Mission Karmayogi : A National Capacity Building Paradigm for Civil Services - Dr. H M Naveen (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Mission Karmayogi is a national scheme that trains the civil servant to maintain a very high standard of conduct and behavior so that one earns the trust of the people and is emulated by his peers and subordinate. It means that all civil servants must be efficient to discharge their responsibilities to the society. Aligned to another dimension of civil servant as a ‘Karmayogi’ the scheme goes beyond body-mind complex for calm and steady behavior by each of them. This scheme also emphasizes on efficiency in action which signifies productive skillfulness to produce maximum results. It means all civil servants must be efficient to discharge their responsibilities to the society. A double dimension of quality as well as quantity ingrained in this philosophy. Civil servants play a vital role in formulating policy and executing its implementation. Therefore, the DoPT, GoI, has issued the “Karmayogi Guidelines” to bring more clarity to the roles and responsibilities of various stakeholders in the training and capacity building land scope, including that of the institutions established under the Mission Karmayogi. All the Departments, including CSTIs and other organizations functioning under their administrative control are instructed to comply with these guidelines. Therefore, the present article has been drafted to introduce all the stakeholders regarding the background of Mission Karmayogi scheme, objectives, Roles of Various Stakeholders like Civil Service Training Institutions (CSTIs), Ministries / Departments, DoPT, Capacity Building Commission and role of SPV – Karmayogi Bharat Funding, Monitoring and Evaluation and lastly, Training and Capacity Building in States. Ultimately, it is hoped that these comprehensive guidelines for training and capacity building of their employees will enable for achievement of citizen centric and effective public service system.